2016
DOI: 10.1038/nplants.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

The DNA demethylase ROS1 targets genomic regions with distinct chromatin modifications

Abstract: The Arabidopsis ROS1/DEMETER family of 5mC DNA glycosylases are the first genetically characterized DNA demethylases in eukaryotes. However, the features of ROS1 targeted genomic loci are not well-understood. In this study, we characterized ROS1 target loci in Arabidopsis Col-0 and C24 ecotypes. We found that ROS1 preferentially targets transposable elements (TEs) and intergenic regions. Compared to most TEs, ROS1-targeted TEs are closer to protein coding genes, suggesting that ROS1 may prevent DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
136
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 45 publications
10
136
1
1
Order By: Relevance
“…As shown in Fig. 2A and consistent with features of AtROS1 targets in Arabidopsis (20), DNA hypermethylation in sldml2 mutant fruits occurred in all three sequence contexts: mCG, mCHG, and mCHH. To confirm the function of SlDML2 in DNA demethylation, we examined DNA methylation levels of the other mutant allele of SlDML2, sldml2-2, and found that the identified SlDML2 targets in sldml2-1 have similar increases in mCG, mCHG, and mCHH levels in sldml2-2 at 60 dpa compared with the WT at 60 dpa (Fig.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…As shown in Fig. 2A and consistent with features of AtROS1 targets in Arabidopsis (20), DNA hypermethylation in sldml2 mutant fruits occurred in all three sequence contexts: mCG, mCHG, and mCHH. To confirm the function of SlDML2 in DNA demethylation, we examined DNA methylation levels of the other mutant allele of SlDML2, sldml2-2, and found that the identified SlDML2 targets in sldml2-1 have similar increases in mCG, mCHG, and mCHH levels in sldml2-2 at 60 dpa compared with the WT at 60 dpa (Fig.…”
Section: Resultssupporting
confidence: 84%
“…These results suggest that, during fruit ripening, SlDML2 may have a function similar to that of AtROS1 in preventing gene silencing by demethylating nearby TEs or highly methylated intergenic regions. However, in contrast to AtROS1, which targets TEs in both euchromatic and heterochromatic regions (20), SlDML2 preferentially targets TEs in euchromatic regions. Boxplots showing DNA methylation levels at combined sldml2-1 hyper-DMRs in WT-46dpa, WT60dpa, two biological replicates of sldml2-1-46dpa, and two biological replicates of sldml2-2-60dpa.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations